Status of Patient-Doctor Communication in a Nepali Hospital - Duwadi, Eak Prasad; Adhikari, Siza; Nepal, Sujan (Birat Journal of Health Sciences, 2022)
Introduction: The dialog of thoughts and information verbally or nonverbally between doctors and patients is patient-doctor communication. This study explores the persuasive quality of patient-doctor communication in a Nepali hospital. With the help of the data collected, the study evaluates mainly ethical appeals, logical appeals and emotional appeals.Objective: The objective of this research is to evaluate the persuasive elements specifically ethos, logos and pathos of patient-doctor communication in a Nepali hospital.Methodology: This is a hospital based descriptive study. This research has used Aristotle’s rhetoric: Ethos, logos and pathos. Because of the lack of big data in this area, secondary data is scanty, so an empirical tool (survey) is adopted for generating data. First a survey is done on 50 doctors working in the hospital, and 300 outpatients suffering from chronic diseases. The data is collected and entered on an Excel file. Later it is analyzed and interpreted thematically with the help of pie charts and tables.Results: Ethical appeals, logical appeals and emotional appeals are found good in patient-doctor communication in this hospital under study. Conclusion: In terms of ethos, logos and pathos separately, patient-doctor communication in Nepali hospital appears to be good. However, there is a lack of combination of all these three elements in most of the respondents.